Risk Factor Analysis of Recurrent Diarrhea on Toddlers in Sumberjambe Health Center Jember Regency - Anita Margaret Wibisono; Ancah Caesarina Novi Marchianti; Dion Krismashogi Dharmawan (Faculty of Medicine, University of Jember, 2020)
Recurrent diarrhea is diarrhea that occurs repeatedly within one to three months. Toddler is the highest group suffering of diarrhea. Diarrhea is the second leading cause of death on toddler. This research aims to analyze the effect of risk factors of recurrent diarrhea on toddler in Sumberjambe Health Center Jember Regency. This type of research is observational analytic with case control design. The sample is 50 cases and 50 controls. The sampling technique used consecutive sampling method. The research was conducted in December 2018 to January 2019 using a questionnaire. Data analysis using Chi Square test and Logistic Regression test. Chi Square analysis results are child’s age (p= 0.003), gender (p= 1,000), exclusive breastfeeding (p= 0.044), measles immunization (p= 0.387), nutritional status (p= 0.840), hand nail hygiene (p= 0.395), mother’s age (p= 0.435), mother’s education level (p= 0.263), mother’s knowledge (p= 0.494), hand washing habit (p= 0.684), and family income (p= 0.773). Logistic Regression analysis results are child’s age (p= 0.002) and exclusive breastfeeding (p= 0.499). The conclusions of this study are child’s age and exclusive breastfeeding have influence of recurrent diarrhea on toddler and child's age is the most influential risk factor of recurrent diarrhea on toddler. The suggestion of this research is that it needs to research other risk factors and mothers are required to give exclusive breastfeeding. Keywords: risk factors, recurrent diarrhea, toddler